2020
DOI: 10.3390/molecules25153356
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ferulic Acid in Angelica sinensis by Temperature-Controlled Hydrophobic Ionic Liquids-Based Ultrasound/Heating-Assisted Extraction Coupled with High Performance Liquid Chromatography

Abstract: Hydrophilic ionic liquids are often used to extract the active ingredients of medicinal plants, while hydrophobic ionic liquids are rarely used to directly extract solid samples. In this paper, a simple, novel and efficient temperature-controlled hydrophobic ionic liquids-based ultrasound/heating-assisted extraction (TC-ILs-UHAE) procedure coupled with high-performance liquid chromatography (HPLC) was developed and applied to the determination of ferulic acid (FA) in Chinese herbal medicine Angelica sinensis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…vulgare and A. sinensis loaded films CD15 and CF15, respectively flaunted the presence of drug particles on the surface as well as inside the polymeric matrix. The particles on the surface of CD15 had small, round and protruding shape which were similar to the appearance of particles of pure A. sinensis described by Wu et al 76 From literature, it was found that the essential oils of F . vulgare were not compatible with chitosan-based films because it damaged the surface and made small pores.…”
Section: Resultssupporting
confidence: 78%
“…vulgare and A. sinensis loaded films CD15 and CF15, respectively flaunted the presence of drug particles on the surface as well as inside the polymeric matrix. The particles on the surface of CD15 had small, round and protruding shape which were similar to the appearance of particles of pure A. sinensis described by Wu et al 76 From literature, it was found that the essential oils of F . vulgare were not compatible with chitosan-based films because it damaged the surface and made small pores.…”
Section: Resultssupporting
confidence: 78%
“…Diels, and ferulic acid is a marker content used to determine the quality of Angelica sinensis (Oliv.) Diels according to the Chinese Pharmacopoeia [44]. In a recent study, Qi et al investigated the effect of ferulic acid on STZ-induced diabetic nephropathy rats and found that ferulic acid improved in ammation, oxidative stress, reduced FBG, TC and TG, as well as attenuated podocyte injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…Diels , and ferulic acid is a marker content used to determine the quality of Angelica sinensis (Oliv.) Diels according to the Chinese Pharmacopoeia [ 42 ]. In a recent study, Qi et al investigated the effect of ferulic acid on STZ-induced diabetic nephropathy rats and found that ferulic acid improved inflammation and oxidative stress, reduced FBG, TC and TG, and attenuated podocyte injury [ 43 ].…”
Section: Discussionmentioning
confidence: 99%